MODERASI TRI HITA KARANA PADA DETERMINAN KINERJA KEUANGAN LPD DI DENPASAR - Ni Putu Trisna Windika Pratiwi; Ni Made Wisni Arie Pramuki; Ni Putu Yeni Yuliantari; Gusti Alit Suputra (Faculty of Economics and Business, Universitas Warmadewa, 2026)
The Village Credit Institution (LPD) in Bali is a hybrid organization that balances financial functions with social goals. This study aims to analyze the effect of organizational structure and financial literacy on LPD financial performance, and to examine the role of Tri Hita Karana (THK) Culture as a moderating variable. The research was conducted on 34 LPDs in Denpasar City with a sample of 97 respondents consisting of the chairman, secretary, and treasurer. Data were analyzed using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. The results showed that organizational structure and financial literacy had a significant positive effect on financial performance. Financial literacy was found to be the most dominant variable. However, the moderation test showed that THK Culture did not significantly moderate the relationship between organizational structure and financial literacy on financial performance. These findings support the Resource-Based View (RBV) theory regarding the importance of internal resources but indicate that THK functions more as a social foundation for legitimacy than a technical moderator of financial performance.